Lessons From Markey et al. (2015) and Bushman et al. (2015): Sensationalism and Integrity in Media Research. (1st April 2015) - Markey, Patrick M.; Males, Mike A.; French, Juliana E.; Markey, Charlotte N.
Abstract: This article presents a response to the comment by B. J. Bushman, D. Romer, and P. E. Jamieson (2015). This reply addresses 2 issues raised by the commenters. First, they claim they and others have not made sensationalistic statements linking violent media to horrific acts of real-world violence. In response, we supply numerous examples of sensationalistic statements made by them and others. Second, they claim they did not expect violence in films to be related to violent behavior among adults, but only among youths. However, by examining homicide arrests and homicide gun mortality rates among youths, we found that as films have become increasingly violent over time, both homicide arrests and gun-related homicides have tended to decrease among this age group.